Development of the clinical assessment scale in autoimmune encephalitis - Lim, Jung‐Ah; Lee, Soon‐Tae; Moon, Jangsup; Jun, Jin‐Sun; Kim, Tae‐Joon; Shin, Yong‐Won; Abdullah, Suhailah; Byun, Jung‐Ick; Sunwoo, Jun‐Sang; Kim, Keun Tae; Yang, Tae‐Won; Lee, Woo‐Jin; et al. (Annals of neurology, 2019)
Objective There is no scale for rating the severity of autoimmune encephalitis (AE). In this study, we aimed to develop a novel scale for rating severity in patients with diverse AE syndromes and to verify the reliability and validity of the developed scale. Methods The key items were generated by a panel of experts and selected according to content validity ratios. The developed scale was initially applied to 50 patients with AE (development cohort) to evaluate its acceptability, reproducibility, internal consistency, and construct validity. Then, the scale was applied to another independent cohort (validation cohort, n = 38). Results A new scale consisting of 9 items (seizure, memory dysfunction, psychiatric symptoms, consciousness, language problems, dyskinesia/dystonia, gait instability and ataxia, brainstem dysfunction, and weakness) was developed. Each item was assigned a value of up to 3 points. The total score could therefore range from 0 to 27. We named the scale the Clinical Assessment Scale in Autoimmune Encephalitis (CASE). The new scale showed excellent interobserver (intraclass correlation coefficient [ICC] = 0.97) and intraobserver (ICC = 0.96) reliability for total scores, was highly correlated with modified Rankin scale (r = 0.86, p < 0.001), and had acceptable internal consistency (Cronbach α = 0.88). Additionally, in the validation cohort, the scale showed high interobserver reliability (ICC = 0.99) and internal consistency (Cronbach α = 0.92). Interpretation CASE is a novel clinical scale for AE with a high level of clinimetric properties. It would be suitable for application in clinical practice and might help overcome the limitations of current outcome scales for AE. ANN NEUROL 2019;85:352–358.